Recombinant Glycoprotein Vaccines for Human Immunodeficiency Virus-Infected Children and Their Effects on Viral Quasispecies - Essajee, Shaffiq M. (American Society for Microbiology, 2002)
In individuals infected with human immunodeficiency virus type 1 (HIV-1), specific immunity is associated with a more diverse viral repertoire and slower disease progression. Attempts to enhance antiviral immunity with therapeutic vaccination have shown that recombinant glycoprotein (RGP) vaccines are safe, well tolerated, and immunogenic, but the effect of RGP vaccines on the viral repertoire is unknown. We evaluated diversification of the viral envelope in 12 HIV-infected children who received placebo or RGP vaccines. At baseline, 11 of 12 patients had multiple viral variants. On follow-up 6 months later, children who had a strong vaccine-associated lymphoproliferative immune response showed less viral diversification than those in whom the immune response was weak or absent. These results suggest that the immune response elicited by RGP vaccines does not exert a significant selection pressure on the viral quasispecies and therefore may not be helpful in changing the course of the disease.